Activated crystalline silicon dioxide mitigates weight loss in lactating sows - Araujo, Lúcio F.; Vitagliano, Luiz A.; Decaux, Caroline; Janssen, Fabiana T.; Sartore, Yasmin G. de Almeida; Granghelli, Carlos A.; Tse, Marcos L. P. [UNESP]; Carvalho, Rachel S. B.; Martins, Simone M. M. K.; da Silva Araujo, Cristiane S. (Taylor & Francis, 2022)
This study investigated activated crystalline silicon dioxide (SIL) supplementation in late pregnancy and lactating sows on reproductive parameters as well as the performance of suckling piglets. Eighty sows were assigned to two groups: control (CON, n = 40), and activated crystalline SIL (n = 40). Both treatments received identical basal diets, without (CON), or with 0.3 kg of activated SIL/ton at day 111 of pregnancy up to day 21 of lactation. The sows were evaluated at day110 of gestation and at day 21 of lactation for individual body weight (BW), backfat (BF), average daily feed intake (ADFI), percentage of BW and BF loss, and milk production. The litter was evaluated for size and BW at birth, and at 21 d old, likewise the preweaning survival percentage. At day 21 lactation, the SIL sows were 2.39% heavier than the CON group. The sows also had an increase of 5.05% in milk yield compared to the CON sows. In addition, SIL sows showed lower weight loss compared to CON sows. The weaned piglets from SIL sows had an increase of 4.43% in BW compared to CON sows. In conclusion, supplementation of 0.03% of activated crystalline SIL applied to late pregnancy, and to lactating sows reduced weight loss and marginally improved the milk yield and BW of piglets at weaning.Highlights The activated crystalline silicon dioxide (SIL) in diets from late pregnancy to lactation reduced body weight loss of sows. Sows that received activated crystalline SIL in late pregnancy and lactating period trended to improve the milk yield in 5.05%. The piglets from sows fed activated crystalline SIL tended to enhance 4.43% in body weight at 21-d old.
Keywords: Backfat; milk yield; silicates; suckling piglets; weaning